2015
DOI: 10.1111/pcn.12337
|View full text |Cite
|
Sign up to set email alerts
|

Current prescription pattern of maintenance treatments for bipolar patients in Korea: A focus on the transition from acute treatments

Abstract: Aims:We examined prescription patterns in maintenance treatment for recovered bipolar patients and compared these with acute treatments.Methods: Using retrospective methods, the bipolar patients in clinical recovery (Clinical Global Impression Bipolar Version score ≤ 2 for 6 months) after acute episode were selected. We reviewed differences between prescription patterns at remission and after a maintenance period of at least 6 months.Results: A total of 340 bipolar disorder patients were selected. During the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Initially, 43 articles were screened for eligibility, of which 33 were excluded for the following reasons: 11 were excluded because they were review articles, 10,3039 9 because they were case reports/series, 9,12,14,18,4044 11 which did not compare changes in disease severity after bupropion treatment or differences in the treatment effect or drop-out or phase-shifting rates with bupropion and other treatments, 15,20,4553 and 1 which was a meta-analysis. 54 The remaining 10 articles were then entered into the current meta-analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, 43 articles were screened for eligibility, of which 33 were excluded for the following reasons: 11 were excluded because they were review articles, 10,3039 9 because they were case reports/series, 9,12,14,18,4044 11 which did not compare changes in disease severity after bupropion treatment or differences in the treatment effect or drop-out or phase-shifting rates with bupropion and other treatments, 15,20,4553 and 1 which was a meta-analysis. 54 The remaining 10 articles were then entered into the current meta-analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 In these studies, bupropion has been reported to be safe and to carry the least risk of phase shifting among other antidepressants based on current evidence. 11,38 However, an increasing number of studies have reported their clinical experience of bupropion usage in clinical practice 4,12,15,20,43,46,55 in recent years, and thus the safety of bupropion with regard to phase shifting needs to be seriously reconsidered. The present study provides up-to-date key information about the safety of bupropion in BD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 9 , 10 The overall prescription change, with replacement of risperidone and olanzapine with quetiapine and the doubling in scripts of lamotrigine, is consistent with a South Korean observational study on the transition from acute to maintenance treatment in BD. 19 The increase in quetiapine use is probably related to its efficacy in treating the emergence of depressive symptoms during maintenance care.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dosing, a Korean study estimated an average total daily dose of lithium carbonate of 970 mg and of disodium valproate at 1082 mg among BD patients recovering from acute episodes of illness. 10 Another Asian study reported on the ratio of the prescribed daily dose of MSs to a defined, standard daily dose, 11 finding a mean ± SD ratio of 0.62 ± 0.29, suggesting relatively conservative dosing. 7 To compare doses of specific MSs, it is helpful to have a way to standardize doses.…”
mentioning
confidence: 99%